2011
DOI: 10.1007/s00774-011-0279-3
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and residual lifetime risk of osteoporosis-related fractures in Korea

Abstract: Although the Korean population does not have high risk for osteoporosis, the numbers of osteoporosis-related fractures represent a considerable economic burden to society. The purpose of this study was to determine the incidence and residual lifetime risk of osteoporosis-related fractures in Korea, using data from the Health Insurance Review and Assessment Service (HIRA), which includes nationwide information compiled by the Korean government. All new visits or admissions to Korean clinics or hospitals for fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 33 publications
1
115
0
Order By: Relevance
“…Chinese women are estimated to have much higher residual lifetime and 10 year risks of osteoporotic clinical vertebral and wrist fractures, but the difference in 10 year risks of hip fractures are relatively small between men and women (Table 3 and Figure 1). The estimated risks of osteoporotic fractures in the Chinese population from our study are consistent with those in previous studies which have been found to be lower than those in Caucasians 7,8,[26][27][28][29] and some other Asian populations 9,10 . However, the residual lifetime hip fracture risk at age 50 years was noticeably higher than the earlier estimation for the Chinese population 11 (Table 4).…”
Section: Discussionsupporting
confidence: 93%
“…Chinese women are estimated to have much higher residual lifetime and 10 year risks of osteoporotic clinical vertebral and wrist fractures, but the difference in 10 year risks of hip fractures are relatively small between men and women (Table 3 and Figure 1). The estimated risks of osteoporotic fractures in the Chinese population from our study are consistent with those in previous studies which have been found to be lower than those in Caucasians 7,8,[26][27][28][29] and some other Asian populations 9,10 . However, the residual lifetime hip fracture risk at age 50 years was noticeably higher than the earlier estimation for the Chinese population 11 (Table 4).…”
Section: Discussionsupporting
confidence: 93%
“…[1,2] Osteoporosis is associated with fragility fractures, which results in decreased activity, poor quality of life, high mortality and excessive economic burden. [2,3,4,5,6] Korean population is aging and osteoporosis has been one of the highlighted health care concerns in Korea. [6]…”
Section: Introductionmentioning
confidence: 99%
“…[2,3,4,5,6] Korean population is aging and osteoporosis has been one of the highlighted health care concerns in Korea. [6]…”
Section: Introductionmentioning
confidence: 99%
“…However, the ICD-10 coding system, established in 1989 by WHO, does include high levels of detail, standardized terminology, and expanded concepts for injuries, and other related factors [16], and is therefore more useful than previous codes used in epidemiologic studies. In addition, we used an age of 50 years or more as an additional criterion to exclude non-OFs, as elsewhere [1,17]. Second,…”
Section: Resultsmentioning
confidence: 99%